Postmodernism Challenges for Muslim Schools and Universities in Malaysia: The Role of AI Pedagogical Integration into Islamic Education - Jamil, Jamaliah; Jamil, Nurul Huda Izzati (Muslim Education Review, 2024)
In today’s rapidly changing world, postmodern civilization has been accused of undermining traditional, religious universal values and socio-economic inequality. The intersection of Islamic philosophy and secular education creates profound tension, as Islamic teachings on justice, equality and religious principles often clash with Western secular values, leading to issues such as incompetent graduates, LGBTQ disorder, and over- capitalism conflicts. Schools and universities also grapple with significant challenges like zero hands-on skills, large class sizes, lack of resources, and student behavioral ongoing issues, which impede effective teaching and learning. Additionally, non-inclusive students, especially those with disabilities or from minority ethnic backgrounds, face bullying, discrimination and difficulty accessing resources, exacerbating their isolation and hindering academic performance. This study utilized a qualitative research methodology grounded in the researchers’ nearly twenty years of teaching experience at private universities across Malaysia, including at UNITAR Malaysia, Limkokwing University of Creative Technology (LUCT), the Management and Science University (MSU), and Tunku Abdul Rahman University College (TARUC). The research was informed by direct classroom engagement, a mentoring program, and involvement in academic events administration, offering deep insights into student challenges and enriching data collection. The methodology included providing motivational support and counseling to students with special needs and those underperforming. A critical, reflexive approach was adopted to address potential biases, and results were verified through member-checking and triangulation. This comprehensive approach enabled a thorough exploration of the Malaysian educational context, identifying challenges and themes, yet providing a robust framework for understanding student experiences and pedagogical strategies. The study is structured into four sections: methodology, challenges in Malaysia’s educational system, the incorporation of Qur’anic metaphysics in tertiary education, and the application of interactive AI-pedagogy technologies. The study revealed practical recommendations for educators, policy makers, and researchers, aiming to bridge the gap between Islamic principles and secular educational practices. Using Malaysia as a case study, the research explores the potential of a holistic approach to Islamic education in addressing the postmodern and post-pandemic challenges by Muslim society. It is worth noting that the study is specifically focused on Muslim education in Malaysia. Therefore, its findings may not be generalizable to other Muslim countries or societies. Nevertheless, the research is expected to provide a profound perspective on addressing postmodernism challenges in the Muslim pedagogical world.